STRATEGI MARKETING SYARIAH DALAM UPAYA MENINGKATKAN PENJUALAN DI TOKO ADZKIA KELURAHAN KEBUN GERAN KOTA BENGKULU - Alfioni, Sovita; B, Idwal; Muttaqin, Faisal (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2023)
Traders or entrepreneurs are required to have a good and reliable marketing strategy so that it does not only sell well in the market but is also able to compete. The purpose of this study is to find out what sharia marketing strategies are and what are the obstacles to sharia marketing and their solutions. This research method uses qualitative research with a descriptive approach. The marketing concept at adzkia stores is in accordance with the four characteristics of marketing in Islam, namely: Theistic (rabbaniyyah), Ethical (akhlaqiyyah), realistic (al-waqiyyah), humanistic (insaniyyah). Obstacles and solutions, serving consumers the solution by providing enthusiasm and motivation, closing the shop at prayer times the solution is sticking paper in front of the store as a form of notification, price competition solutions explaining to consumers that price is in accordance with quality, there is still a lack of interest in Muslim fashion the solution is selling contemporary products.